Plan de negocio para la realización de una fabrica y comercializadora de calzado en la ciudad de Santa Marta - Jauregui Taha, Valentina (Universidad Antonio Nariño, 2022)
Abstract The project consists of the design, production and commercialization of footwear for men, women and children; for the population of the city of Santa Marta and nationwide. The project seeks to publicize the products through social networks and instant messaging applications, such as a website, Facebook, WhatsApp, as well as direct marketing tools such as the written press at the regional level according to to the opening of the market; Consequently, it will also be marketed in direct factory stores and through selected distributors, according to a profile necessary for this business plan. Subsequently, a detailed study will be carried out where the behavior of the market is analyzed, according to what is related to quality and prices. Similarly, the business proposal is based on the factory's own models, with the aim of covering the market in the city of Santa Marta, in such a way that good results can be achieved.